Islam, Judaism, and Zoroastrianism (Encyclopedia of Indian Religions,, 2018)
The earlier volume in this series dealt with two religions of Indian origin, namely, Buddhism and Jainism. The Indian religious scene, however, is characterized by not only religions which originated in India but also by religions which entered India from outside India and made their home here. Thus religious life in India has been enlivened throughout its history by the presence of religions of foreign origin on its soil almost from the very time they came into existence. This volume covers three such religions-Zoraoastrianism, Judaism, and Islam . In the case of Zoraostianism, even its very beginnings are intertwined with India, as Zoroastrianism reformed a preexisting religion which had strong links to the Vedic heritage of India. This relationship took on a new dimension when a Zoroastrian community, fearing persecution in Persia after its Arab conquest, sought shelter in western India and ultimately went on to produce India's pioneering nationalist in the figure of Dadabhai Naoroji ( 1825-1917), also known as the Grand Old Man of India. Jews found refuge in south India after the destruction of the Temple by the Romans in 70 C.E. and have remained a part of the Indian religious scene since then, some even returning to Israel after it was founded in 1948. Islam arrived in Kerala as soon as it was founded and one of the earliest mosques in the history of Islam is found in India. Islam differs from the previously mentioned religions inasmuch as it went on to gain political hegemony over parts of the country for considerable periods of time, which meant that its impact on the religious life of the subcontinent has been greater compared to the other religions. It has also meant that Islam has existed in a religiously plural environment in India for a longer period than elsewhere in the world so that not only has Islam left a mark on India, India has also left its mark on it. Indeed all the three religions covered in this volume share this dual feature, that they have profoundly influenced Indian religious life and have also in turn been profoundly influenced by their presence in India.